Politics under the Influence : Vodka and Public Policy in Putin's Russia - Bailey, Anna L. (Book collections on Project MUSE., 2018)
"The first English-language book on Russian alcohol policy in the post-Soviet period; a study of the realities of contemporary Russian policymaking, governance, and cronyism"--